2010
DOI: 10.1158/1538-7445.am10-3996
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3996: Genomic analysis in breast cancer cells after metallothionein-2A silencing

Abstract: Introduction Breast cancer is the most prevalent type of cancer reported in women and mammoth effort has been put in to understand its etiology. Metallothionein (MT), a divalent cation binding protein, was previously shown to be associated with histopathological parameters of breast cancer and mediated cancer progression. MTs belong to a family of ubiquitous, low-molecular weight house-keeping proteins. In human, 10 known functional isoforms of MT, namely 1A, 1B, 1E, 1F, 1G, 1H, 1X, 2A, 3 and 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…MT-1F has been positively correlated with malignancy grade (Jin et al, 2001), whereas MT-1E expression has been found in estrogen receptor-negative breast cancer cell lines (Friedline et al, 1998;Jin et al, 2001). In addition, MT-2A has been identified as the most abundant in breast cancer and plays a protective role in these cancer cells, with high expression involved in cell cycle regulatory capabilities (Lai et al, 2010;Lai et al, 2011). MT overexpression can also induce other proteins, e.g., MT-2A induces the overexpression of MMP-9 with subsequent induction of the invasive phenotype of breast cancer cells (Emri et al, 2013).…”
Section: The Role Of Mts In Tumor Metastasismentioning
confidence: 99%
“…MT-1F has been positively correlated with malignancy grade (Jin et al, 2001), whereas MT-1E expression has been found in estrogen receptor-negative breast cancer cell lines (Friedline et al, 1998;Jin et al, 2001). In addition, MT-2A has been identified as the most abundant in breast cancer and plays a protective role in these cancer cells, with high expression involved in cell cycle regulatory capabilities (Lai et al, 2010;Lai et al, 2011). MT overexpression can also induce other proteins, e.g., MT-2A induces the overexpression of MMP-9 with subsequent induction of the invasive phenotype of breast cancer cells (Emri et al, 2013).…”
Section: The Role Of Mts In Tumor Metastasismentioning
confidence: 99%